Leadership Styles of Nurse Managers and Job Satisfaction of Staff Nurses: Correlational Design Study - Albagawi, Bander (European Scientific Journal, ESJ, 2019)
Aim: This study aimed to determine the relationship between the leadership styles of nurse managers and the job satisfaction of staff nurses in hospital settings in Ha’il City, Saudi Arabia. Methods: The study employed a quantitative correlational research design. The research respondents were staff nurses working under the supervision of nurse managers, who they evaluated for leadership styles, using the multifactor leadership questionnaire developed by Bass and Avolio (1992). At the same time, the staff nurses rated their job satisfaction using the work quality index questionnaire by Whitley and Putzier (1994). Purposive sampling was employed to generate samples of staff nurses from four governmental hospitals in Ha’il City. Findings: The leadership styles of nurse managers, as perceived by the staff nurses, revealed that they were often displaying transformational leadership (M = 2.88), sometimes displaying transactional leadership (M = 2.31) and occasionally displaying laissez-faire leadership (M = 1.38). The staff nurses’ level of job satisfaction yielded responses of ‘somewhat satisfied’ for professional work environment (M = 4.78) and professional relationships (M = 4.95) and ‘neutral’ for autonomy (M = 4.45), work worth (M = 4.5), role enactment (M = 4.34) and benefits (M = 4.23). Transformational leadership correlated with the level of job satisfaction, and yielded an r-value of 0.258, which connoted a low correlation, with a p-value of 0.000. There was a significant relationship between the nurse managers’ transformational leadership style, as perceived by the staff nurses, and the staff nurses’ level of job satisfaction. This implies that, because the nurse managers often manifested transformational leadership, the staff nurses’ level of job satisfaction slightly increased. Moreover, there was a significant relationship between laissez-faire leadership and level of job satisfaction (p-value of 0.006), with a correlation coefficient of ˗0.204 indicating a negative correlation between variables. Conclusion: The nurse managers displayed transformational leadership behaviour more than transactional and laissez-faire leadership styles. The staff nurse respondents were somewhat satisfied with their work environment and professional relationships; however, they were unsure whether they were satisfied with factors such as autonomy, work worth, role enactment and benefits - as reflected in their neutral responses. Transformational leadership styles positively correlated with the nurses’ job satisfaction.